Pengaruh Pemberian Aromaterapi Essential Oil Lavender Terhadap Peningkatan Kuantitas Tidur Anak di Panti Asuhan Anak Malang - Nadhifah Rahmawati; Lembah Andriani; Nurul Anjarwati; Astrid Ester Hayer (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Sleep is something that is needed and must be fulfilled by humans. Children need enough sleep for good health status. Without balanced sleep, it will encourage the emergence of developmental problems and serious health problems. Based on the results of previous studies, it shows that 50.9% of preschool children have a sleep quantity of less than 10 hours. Therefore, the purpose of this study was to determine the effect of giving lavender essential oil on increasing the sleep quantity of children at the Malang Orphanage. This research method is quantitative research with the type of research used is quasi-experimental with a one group pre-post test design. The sampling technique used in this study is non-probability sampling with a sample size of 30 children. In this study, the Paired t-test was used as a parametric test to determine whether or not there was a difference in the quantity of children's sleep before and after being given the aroma of lavender essential oil. This study was conducted on October 2-8, 2024 in Malang Orphanage. The instruments used in this study were the SOP for administering lavender essential oil aromatherapy and observation sheets and evaluation sheets. The results of this study indicate that there is a difference in the average between before and after being given lavender essential oil aroma, with an average of 7.23 hours of sleep per day before the intervention and 8.54 hours per day after the intervention. Meanwhile, the results of the difference test using the Paired t-test showed a significant value or p value = 0.000 (p <0.05). The conclusion of this study indicates that there is a significant effect of administering lavender essential oil aromatherapy on the quantity of sleep of children in Malang Orphanage. Further researchers are expected to be able to develop research by further examining the duration of respondents' naps in order to accumulate the duration of sleep per day of respondents as a whole. In addition, nurses as caregivers and the community can also apply the results of this study as an effort to increase the quantity of sleep in children.